Ethics in Neonatology - Reza Saeidi (Mashhad University of Medical Sciences, 2024)
Decisions about neonatal end-of-life care have been done in several countries and Neonatal ethics must answer several basic questions:Is withholding potentially life-saving treatment from infants morally justified?What are the necessary criteria for stopping treatment in cases of futile and ineffective treatment?Who has the authority to make decisions for a critically ill baby? Abandoning life-saving treatment is definitely not morally justified, but if the treatment is useless and we are faced with an incurable disease, is it necessary to continue the treatment? And is stopping treatment morally wrong?We definitely need scientific and evidence-based protocols for any decision to stop the treatment of an incurable patient.The first 28 days of life - the neonatal period - is the most vulnerable time for a child's survival. According to UNICEF January 2023 statistics: Globally, 2.3 million children died in the first month of life in 2021 - approximately 6,400 neonatal deaths every day. One of the successful interventions in reducing infant mortality is overcoming ethical challenges in infant care and treatment. Failure to comply with the laws and code of ethics in some special care departments for newborns can cause challenges. Codes of ethics are general principles, rules and standards, including ethical standards and guidelines for the performance of employees in their roles. When ethical codes are followed in the provision of health care services, the quality of care is improved.The Groningen Protocol created in 2004 by Eduard Verhagen, at the University Medical Center Groningen (UMCG) in Groningen, the Netherlands. It contains directives with criteria under which physicians can perform "active ending of life on infants" (child euthanasia) without fear of legal prosecution.[1][2][3]  and has been ratified by the Dutch National Association of Pediatricians.[4]The protocol, drawn up after extensive consultation between physicians, lawyers, parents and the Prosecution Office, offers procedures and guidelines to achieve the correct decision and performance. The final decision about "active ending of life on infants" is not in the hands of the physicians but with the parents, with physicians and social workers agreeing to it. Criteria are, amongst others, "unbearable suffering" and "expected quality of life". Only the parents may initiate the procedure. The procedure is reported to be working well.[5]For the Dutch public prosecutor, the termination of a child's life (under age 1) is acceptable if four requirements were properly fulfilled:The presence of hopeless and unbearable suffering.The consent of the parents to termination of life.Medical consultation having taken place.Careful execution of the termination.[5]Doctors who end the life of a baby must report the death to the local medical examiner, who in turn reports it to both the district attorney and to a review committee.